The possibilities of ethical behaviour in organisations: a study of managerial selves - Cefai, Michael J. (2012)
This thesis is a study of managerial selves and their possibilities for ethical behaviour within organisations. It explores the risks to managerial ethical behaviour and also the possibilities for doing ethics within organisations.